An overview of the factors affecting the mechanical properties of recycled concrete - Fathollah Sajedi (Iranian Society of Structrual Engineering (ISSE), 2019)
Concrete, as one of the main components of the manufacturing industry since the beginning of the process of production, operation and destruction, plays a major role in the creation of environmental pollution. Since more than 70% of the main body of concrete is aggregate, the promotion of culture and considerations based on the principles of sustainable development in design, construction and demolition process of concrete is of great importance. One of the basic principles of sustainable development is the importance of recycling. Recycling of damaged concrete in the last century has become one of the most important interests of researchers. So, after studying and recognizing their durability and mechanical properties (MP’s), today in developed countries, the necessary relationships for the recognition of structural performance of these concretes is under construction. The purpose of this research is to investigate the results of research carried out in different countries in the field of recognition of the MP’s of recycled concretes (RC’s). More than 80 articles published in prestigious technical journals were examined and classified together in the six groups that the researchers considered in analyzing the MP’s of RC’s. The effect of each of these groups on compressive and tensile strengths and elasticity of concrete were studied. The results showed that the type, size and quality of recycled aggregates (RA’s) are very effective in determining the level of replacement of recycled materials (RM’s) in concrete. Curing conditions, water reducing and pozzolanic materials, although effective in improving the MP’s of RC’s, cannot reduce the adverse effects of increasing the replacement of RM’s on the mechanical properties of concrete. Concerning the effect of age on the mechanical properties of RC’s, it is common ground that some of these properties are similar to conventional ones.